Childbirth and Postpartum Period Fear in Pregnant Women and the Affecting Factors - Nuray Egelioğlu Cetişli; Zubeyde Denizci Zirek; Fatma Bakılan Abalı (Universidad de La Sabana, 2015)
Objective: The aim of this study was to identify the anxiety pregnant women feel about childbirth and the postpartum period and to determine the affecting factors. Methods: A descriptive design was used in the study, which was conducted with pregnant women at two obstetric polyclinics of a university hospital in Turkey from January 2014 to July 2014. The population consisted of 143 pregnant women. The data were collected using an individual identification form and the Fear Childbirth and Postpartum Anxiety Scale. The percentage, Kruskall Wallis, Mann-Whitney U and Independent Sample t tests were used to evaluate the differences between the variables. Results: The results of the study reveal that pregnant women are quite fearful of childbirth and the postpartum period. Conclusions: It is necessary to decrease fear of childbirth, because of its negative effects. Doi: 10.5294/aqui.2016.16.1.5